2019
DOI: 10.5530/pj.2019.11.67
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium polyanthum (Wight) Walp: A Potential Phytomedicine

Abstract: Syzygium polyanthum (Wight) Walp is well known among Malaysians as "salam", "serai kayu", or "samak kelat", whereas in Indonesia, the plant is commonly recognized as "ubar serai", "meselengan", "manting", Indonesia laurel, or Indonesian bay leaf. 1 The scientific name S. polyanthum was usually used in synonymous with Eugenia polyantha. 2 According to the Archive of "Catalogue of Life", 3 this plant belongs to Plantae kingdom, Magnoliophyta phylum, Magnoliopsida class, Myrtales order, Myrtaceae family, Syzygiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 25 publications
1
45
0
12
Order By: Relevance
“…The use of leaves as spices is similar reported in Sikkim, Manipur and Tripura, and Arunachal Pradesh (Gudade et al 2015;Salam and Jamir 2016;Chakraborty and Chaturvedi 2015;Bharali et al 2017). The leaves were mainly used for flavoring and seasoning which may be due to the presence of active secondary metabolites than other parts of the plants (Hidayati et al 2017;Ismail and Ahmad 2019). Tamiang tribe use of Alpinia galanga, Curcuma longa, Zingiber officinale as spices.…”
Section: Diversity Of Plants Used As Spice and Condimentsmentioning
confidence: 57%
“…The use of leaves as spices is similar reported in Sikkim, Manipur and Tripura, and Arunachal Pradesh (Gudade et al 2015;Salam and Jamir 2016;Chakraborty and Chaturvedi 2015;Bharali et al 2017). The leaves were mainly used for flavoring and seasoning which may be due to the presence of active secondary metabolites than other parts of the plants (Hidayati et al 2017;Ismail and Ahmad 2019). Tamiang tribe use of Alpinia galanga, Curcuma longa, Zingiber officinale as spices.…”
Section: Diversity Of Plants Used As Spice and Condimentsmentioning
confidence: 57%
“…polyanthum and O. xcitriodorum, both are aromatic plants, are rich in essential oils. S. polyanthum leaves contained higher volatiles compound but lower total phenolics content as compared to S. polyanthum bark (Ismail & Wan Ahmad, 2019). A comparison of essential oils content and composition between several species of Ocimum revealed that O. citriodirum had the least essential oil yield as compared to O. basilicum, O. virride, and O. kilimandscharicum (Rawat et al, 2017).…”
Section: The Moisture Content Of the Dry Samples And Yields Of Extractmentioning
confidence: 92%
“…Namun, selain manfaatnya sebagai penyedap makanan, daun salam ternyata juga menyimpan banyak manfaat lain bagi kesehatan. 7 Penelitian ini dilakukan untuk mengetahui potensi ekstrak etanol 96% dalam menghambat pertumbuhan kanker serviks dengan mengamati ekspresi p53 pada sel HeLa. Hasil penelitian diharapkan mampu memberikan informasi mengenai potensi daun salam sebagai antikanker.…”
Section: Pendahuluanunclassified
“…8 Identifikasi , asam lemak (asam palmitat, asam stearat), asam lemak ester (metil oleat, metal palmitat), diterpen alkohol (phytol), steroid (β-sitosterol). 7,18 Efek pemberian ekstrak etanol daun salam terhadap ekspresi p53 pada sel HeLa Protein p53 merupakan protein yang diekspresikan oleh gen p53 dan telah diketahui memiliki peranan penting dalam pengendalian siklus sel dan kematian sel yang terprogram. 19 Selain itu, p53 juga merupakan regulator utama pada berbagai proses biologis, antara lain autofagi, diferensiasi sel, dan tumor microenvironment remodeling.…”
Section: Alat Dan Bahanunclassified